Optimization of Transaction Database Design with MySQL and MongoDB - Mumtahana, Hani Atun (Politeknik Ganesha Medan, 2022)
Database is one of the most important parts in running an application. Databases can be used to store data. However, in running an application, the selection of an appropriate database needs to be considered, so that the resulting information can be in accordance with user needs. In developing applications, more people use RDBMS design which has a very structured nature, but technological developments have introduced NoSQL as a database development method. In this research, MySQL and MongoDB databases will be tested in transaction processing. The tests carried out include comparisons of database designs, comparisons of defining table structures, comparisons of running time in the insert, update, delete, search processes. The test results show that MongoDB has a simpler table description structure than MySQL. The results of the running time test show that MongoDB has a faster running time difference than MySQL. In the insert process there is a time difference of 0.005625 sec, update 0.001688 sec, delete 0.00075 sec and search 0.006875 sec.